PENGARUH PENAMBAHAN MADU TERHADAP AKTIVITAS ANTIOKSIDAN MINUMAN BELUNTAS-TEH HITAM DENGAN PERBANDINGAN 25:75% (B/B) - D., Eunike Intar; Widyawati, Paini Sri; Budianta, Dwi Wibawa (Jurnal Teknologi Pangan dan Gizi, 2016)
Pluchea indica Less plant usually only used as fresh vegetables and traditional medicine. Beluntas leaf contains many phytochemical compounds that act as antioxidants to prevent free radical. One of alternative utilization beluntas leaf is used as a drink that was packed in tea bag which is substituted black tea at 25: 75% (w/w) proportion and the addition of honey. This research was aimed to determine honey additon effect of antioxidants activity in Pluchea indica Less-black tea drink. The research design used was randomized block design with single factor. Factor that was researched is honey addition (P1, P2, P3, P4, P5, P6) on Pluchea indica Less-black tea drink at 25:75% (w/w) proportion. Each treatment was repeated four times. The results showed that honey additon effect of antioxidants activity in Pluchea indica Less-black tea drink. The addition of honey in Pluchea indica Less-black tea drink with various concentrations produced the total phenols ranged from 481.06-632.94 mg GAE/L sample, the total flavonoids ranged from156.18-196.80 mg CE/L sample, the DPPH free radical scavenging activity ranged from 324.13-389.49 mg GAE/L sample, and the iron ion reducing power ranged from 304.80-401.80 mg GAE/L sample. The antioxidant activity of Pluchea indica Less-black tea honey drink positively correlated with total phenols and total flavonoids. The addition honey in Pluchea indica Less-black tea drink to get the hightest antioxidant activity was P6 that had the hightest total phenol and flavonoid.